Sex differences in anatomic features linked to anterior cruciate ligament injuries during skeletal growth and maturation - Hosseinzadeh, S.; Kiapour, A. M. (The American Journal of Sports Medicine, 2020)
Background: Several anatomic features of the knee have been shown to affect joint and anterior cruciate ligament (ACL) loading and the risk of subsequent injuries. While several studies have highlighted sex differences between these anatomic features, little is known on how these differences develop during skeletal growth and maturation.